Determination of Thyroid Volume by Ultrasonography among Schoolchildren in Philippines. (22nd May 2012) - Kim, Bu Kyung; Choi, Young Sik; Oak, Chul Ho; Park, Yo-Han; Kim, Jae Hyun; Park, Dae Jin; Mora, Cindy; Wilson, Donald; Park, Eun-Kee
Abstract : Objective . Iodine deficiency is defined by the goiter and the urinary iodine concentration. However, a lack of local thyroid volume reference data resulted in the vague definition of goiter, especially in school-aged children. The aim of this paper was to determine the thyroid volumes by ultrasonography in schoolchildren aged 6 to 12 years living in Cagayan areas in Philippine. Methods . Cross-sectional thyroid ultrasonographic data of 158 schoolchildren aged 6–12 years from Tuguegarao and Lagum in Cagayan valley, Philippine were used. Thyroid volumes were compared based on logistic issue and urban and rural area and compared with other previously reported data. Results . The mean values of thyroid volume in Tuguerago and Lagum were 2.99 ± 1.34 mL and 2.42 ± 0.92 mL. The thyroid size was significantly in association with age (P < 0.00 ), weight (P < 0.00 ), height (P < 0.00 ), and BSA (P < 0.00 ) by Pearson's correlation. The median thyroid volumes of schoolchildren investigated in this study were generally low compared to international reference data by age group but not by BSA. Conclusions . We propose for the first time local reference ultrasound values for thyroid volumes in 6–12 aged schoolchildren that should be used for monitoring iodine deficiency disorders.